PEMETAAN SUSEPTIBILITAS MAGNETIK DAN PENENTUAN KANDUNGAN LOGAM PADA AIR GAMBUT DI KELURAHAN TUAH MADANI KECAMATAN TAMPAN PEKANBARU - Siti Alisna; Salomo Sinuraya (Komunikasi Fisika Indonesia, 2021)
Research on mapping the value of magnetic susceptibility and determination of metal content in peat water in Tuah Madani Village, Tampan District, Pekanbaru has been carried out. Samples were taken with each distance 50 meters to the north and east at 64 different points of 150 ml. The results of the calculation of susceptibility with the Quincke method obtained the lowest susceptibility value of 1.551 × 10-5 and the largest of 1.760 × 10-5. AAS test results and susceptibility calculations indicate that the peat water under study is paramagnetic. Mapping of magnetic susceptibility was carried out using the surfer 11 application while determining the metal content using AAS. The sample density was measured to produce values at intervals of 989,000 kg/m3 to 998,000 kg/m3. AAS test results were carried out on five samples chosen based on the value of magnetic susceptibility with the measured parameters namely Mn, Zn, Cr and Mg. Based on the standard threshold value of heavy metals as pollutants, it is known that the content of Mn, Zn, Cr and Mg. Mg in this peat water sample is still categorized as safe because it has not exceeded the standard threshold so it is suitable to be in the environment and not pollute the environment. Testing the parameters most contained in the sample are Mg.